Prognostic impact of the activation status of the Akt/mTOR pathway in synovial sarcoma. Issue 19 (16th July 2013) - Setsu, Nokitaka; Kohashi, Kenichi; Fushimi, Fumiyoshi; Endo, Makoto; Yamamoto, Hidetaka; Takahashi, Yusuke; Yamada, Yuichi; Ishii, Takeaki; Yokoyama, Koichirou; Iwamoto, Yukihide; Oda, Yoshinao
<x xml:space="preserve">Abstract</x> BACKGROUND The Akt/mammalian target of rapamycin (mTOR) pathway, downstream from phosphatidylinositol 3‐kinase (PI3K), mediates cell survival and proliferation. Although this pathway reportedly contributes to the progression of synovial sarcoma, its prognostic impact has not been clarified. METHODS The authors analyzed clinicopathologic data and phosphorylation status of Akt (a serine/threonine kinase also known as protein kinase B), mTOR, the eukaryotic translation initiation factor 4E binding protein (4E‐BP1), and the S6 ribosomal protein by immunohistochemical analysis of 120 formalin‐fixed, paraffin‐embedded samples and by Western blot analysis of 24 frozen samples from 112 patients with synovial sarcoma. RESULTS Akt, mTOR, 4E‐BP1, and S6 were activated in 76.5%, 67.6%, 59.6%, and 42.6% of samples, respectively. Immunohistochemically positive phosphorylated (p) mTOR (pmTOR) and p4E‐BP1 results were correlated with higher mitotic activity, and positive p4E‐BP1 results were correlated with greater necrosis. No mutations around the hot spots in the PI3K catalytic subunit α (PI3KCA) and Akt1 genes were observed. In multivariate analysis of clinicopathologic parameters, frequent mitosis was a risk factor for shorter overall survival; and male sex, visceral location, larger tumor size, and frequent mitosis were identified as risk factors for shorter event‐free survival. Positive pmTOR and p4E‐BP1 results were correlated significantly with shorter overall survival, and positive p4E‐BP1 results were correlated with shorter event‐free survival in univariate analysis. Positive pAkt results were associated significantly with shorter event‐free survival in multivariate analysis. CONCLUSIONS In this study, the Akt/mTOR pathway was activated and was associated with worse clinical and pathologic behavior in patients with synovial sarcoma. The authors propose that this pathway may have potential as a therapeutic target. Cancer 2013;119:3504–3513.. © 2013 American Cancer Society.